A case of adenoviral covid-19 vector vaccine possibly linked to severe but reversible interstitial lung injury post-vaccination. Issue 9 (2nd September 2022) - Liatsos, George D.; Mavroudis, Andreas; Iliakis, Panayiotis; Karmpalioti, Maria; Koullias, Emmanouil; Vassilopoulos, Dimitrios
Abstract: Background: Several safe and effective vaccines against nCoV-19 have been developed to contain the pandemic with very few severe adverse-reactions reported. Vaccine-induced interstitial lung disease (ILD) is a very rare and difficult to recognise and diagnose adverse-reaction and is mostly associated with Influenza vaccines. Methods: We report a 55-yr old male who presented with severe respiratory failure that required for several days oxygen supplementation with high flow nasal cannula, and myocardial infarction. Symptoms onset was eighteen days after the first shot of adenoviral AZD1222 vector vaccine. Possible SARS-CoV-2 natural infection post-vaccination was excluded with rigorous laboratory work-up including multiple nasopharengeal rt-qPCR tests for SARS-CoV-2 detection and close monitoring of his serum SARS-CoV-2 antibodies. Other potential infectious agents and alternate diagnoses were thoroughly investigated. Results: Patient responded impressively to high dose steroids. A repeat chest CT nine days after the first one showed a remarkable resolution of the bilateral ground glass opacities. Except for his cardiology medication, no supplemental oxygen neither steroids were prescribed upon his discharge. On one month follow-up, no residual pulmonary dysfunction was noticed with patient preserving a SatO2 of 97–98% on ambient air. Conclusion: Vaccine-induced ILD might constitute a rare nCoV-19 post-vaccination adverse-event. According to current restricted data, when post-vaccination ILD is early suspected and recognised, then prompt implementation of steroid treatment reverses significantly the lung lesions without progression to fibrosis.